The ‘Strange Kinship’ of Interanimality. Vision, Visibility and Lifeworlds in Science and Art - Daly, Anya (Captures)

(untitled) (Figura, Centre de recherche sur le texte et l'imaginaire, 2022)
The sovereign gaze of the human subject has predominated in natural science and aesthetics across representations of animality and animal lifeworlds. Nonetheless, exceptions to such sovereign gazes, characterised by distantiation, hierarchies, dichotomies of gazer and gazed-at, are found in the work of von Uexküll and da Vinci, in the exceptional quality of attention they bring to their tasks; a transformative attention, revealing as Merleau-Ponty describes “a strange kinship” of interanimality.